2009
DOI: 10.5380/abpr.v38i0.16413
|View full text |Cite
|
Sign up to set email alerts
|

Malacofauna de três fitais da Praia de Caiobá, Matinhos, Paraná

Abstract: Malacofauna de três fitais da Praia de Caiobá, Matinhos, Paraná

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
12

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 20 publications
(25 reference statements)
0
2
1
12
Order By: Relevance
“…In comparison with some of the main studies conducted in Brazil on the malacofauna associated with macroalgae (e.g. Jacobucci et al, 2006;Lacerda et al, 2009;Leite et al, 2009), the present study found the greatest number of species.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In comparison with some of the main studies conducted in Brazil on the malacofauna associated with macroalgae (e.g. Jacobucci et al, 2006;Lacerda et al, 2009;Leite et al, 2009), the present study found the greatest number of species.…”
Section: Discussioncontrasting
confidence: 60%
“…Jacobucci et al, 2006;Lacerda et al, 2009;Leite et al, 2009), Bittiolum varium, columbellids and pyramidellids, for example, represented the most abundant and frequent species, which reinforces even further the importance of macroalgae for many organisms, especially small species. This fauna is composed of species that have an average size of 2 to 3 mm and represent a great challenge in the detection and identification of specimens, which are therefore often underestimated in faunistic surveys.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Porém, fatores físicos como temperatura, radiação solar e variação de marés podem interferir na distribuição e/ou diversidade das espécies no substrato (ABSHER, 1982;NYBAKKEN,1997;SCROSATI & HEAVEN, 2007). Dentre os invertebrados, os bivalves e gastrópodes podem ser considerados como grupos abundantes em substratos rochosos de região entremarés (ABSHER, 1982;LACERDA et al, 2009). Entretanto, em relação aos gastrópodes, a maior mobilidade e as diferentes formas de alimentação (LEITE et al, 2011) os diferem dos demais moluscos que ocorrem nestas regiões, além de serem utilizados como indicadores de contaminação ambiental e das diferentes faixas dos costões rochosos (BAUER et al, 1995, LEITE et al, 2011, CASTRO et al, 2012.…”
Section: Introductionunclassified
“…Os gastrópodes podem ser considerados como um dos grupos mais abundantes da malacofauna presentes em substratos rochosos de região entremarés, (ABSHER, 1982;LACERDA et al, 2009). Dentre as espécies de gastrópodes que constituem a malacofauna da costa sul do litoral brasileiro, destacam-se as espécies de arqueogastropodes Fissurella clenchi e Lottia subrugosa (RIOS, 2009;ROSENBERG, 2013).…”
Section: Introductionunclassified